Pengaruh Kualitas Layanan terhadap Keputusan Pemilihan Tempat Pendidikan (Studi pada TK Raudlatul Jannah Pepelegi Waru - Sidoarjo) - Rahmawati, Indah (BISMA (Bisnis dan Manajemen), 2018)
The service quality is an advantage that is expected and the control towards this advantage is managed to meets the needs and expectations of the customers. Every business must have good service quality, this apply to in educational institutes services. The quality is an important point of consideration for purchasing. Education has very important role in development and progress of next generation of a nation. Kindergarten or pre school education is a golden ages which is in this ages, a child will be easy to accept and remembering a lesson. To assess the service quality using service quality dimension with indicators such as, (1) tangible: buildings, library, worship area, policlinic, canteen, parking lot, sport square, playground, (2) reliability: students programming, (3) responsive: serving students academic, serving students administration, responsive toward problems, (4) assurance: high quality teacher, security, serving in hospitable and friendly attitude, (5) empathy: information of teach and learn process, student-teacher interaction, students participation opportunity, providing solution. This research is trying to understand whether the service quality in educational institutes can affecting the students parent in making decision simultaneously and partially in choosing of TK Raudlatul Jannah. The population of this research is the students parent of TK Raudlatul Jannah, with the sample total of 56 parents, using saturated sampling technique. The analysis technique being used is the multiple linier regression and simple linier regression. The research using multiple linier regression acquired the significant influence from service quality variables is 77% to the decision of students parent in preferring educational institutes variable. The result from simple linier regression test there are influence oaf each variables. The influence of tangbles variable is 44,3%, reliability variable is 42,7%, responsiveness variabel is 53,7%, assurance variable is 48,5%, and emphaty variable is 46,4% to the dicision students parent in preferring educational institutes.